Effects of human Toll-like receptor 1 polymorphisms on ageing - Uciechowski Peter; Oellig Eva Maria; Mariani Erminia; Malavolta Marco; Mocchegiani Eugenio; Rink Lothar (Immunity & Ageing, 2013)
Abstract Background Advanced age results in crucial alterations of the innate and adaptive immune system leading to functional defects resulting in infection and chronic diseases. Toll-like receptors (TLR) recognize pathogenic structures and are important in the immune response to infections and vaccination. However, the role of TLR single nucleotide polymorphisms (SNP) is poorly understood in the setting of human ageing. This study investigated the impact of the TLR1 SNPs A743G and T1805G on ageing in different age groups from two European populations. Results The TLR1 genotypes 743AA/1805GG (TLR1neg) are associated with a TLR1 negative phenotype, impaired function and susceptibility to tuberculosis. Carriers of heterozygous 743AG/1805TG and homozygous 743GG/1805TT genotypes (TLR1pos) have a TLR1 positive phenotype. By comparing healthy young and old German donors, the old group showed a tendency to carry more TLR1neg and less homozygous TLR1pos genotypes. Anti-inflammatory Interleukin (IL)-1 receptor antagonist (Ra) was significantly elevated in supernatants of mononuclear cells from old German subjects with a TLR1pos genotype in contrast to those with the 743AA genotype. Healthy old individuals and nonagenarians from Italy displayed significantly higher frequencies of TLR1pos genotypes than the old group from Germany. The data show that tumor-necrosis-factor (TNF)α, CXCL8 and CCL2 levels were higher in old donors from Germany than in plasma levels from old Italian donors. TNFα and CCL2 levels were significantly raised in old German individuals compared to Italian nonagenarians. German and Italian donors with the TLR1neg genotype basically produced more CCL2 than older European donors with TLR1pos genotypes. Conclusion The higher frequency of the TLR1pos genotype in elderly Italian subjects may result from different ethnic populations. Lower inflammatory mediator release of aged Italian individuals is probably due to different background in nutrition, diet, genetics and to psychological aspects. Elderly donors carrying TLR1pos genotypes basically release more anti-inflammatory IL-1Ra and less inflammatory CCL2 suggesting a decline of the pro-inflammatory status found in ageing and, therefore, this may define an anti-inflammatory phenotype. Future studies are needed to elucidate the association of a TLRpos genotype with decreased susceptibility to infections and reduced risk to develop artherosclerosis.